Using FatSecret application to foster student’s critical nutrition habits - Mutiarani, Afifi; Juwita, Juju; Widodo, Ari (Assimilation: Indonesian Journal of Biology Education, 2025)
Obesity is a global health problem that requires education-based solutions. This study aims to provide students with critical habits in choosing food through biology learning based on the FatSecret application on digestive system material. The research method used a pre-experimental approach with a one-group pretest-posttest design, involving 29 grade XI students. The learning design was developed based on the ADDIE instructional design model. The research instrument was a questionnaire of students' awareness of healthy eating patterns, which is based on eight points of recommendations from the Ministry of Health, as well as a questionnaire of students' responses to learning. The results showed that the majority of students experienced positive changes in healthy eating habits after learning, with 50.6% of students showing an increase in critical awareness. The FatSecret app proved effective in helping students record and analyze daily food consumption data. A total of 62% of students stated that the learning helped them plan a healthy diet, while 75.9% felt more aware of their food consumption. However, there were challenges such as students' difficulty in developing realistic action steps and limited understanding of nutrition. This activity confirms that technology integration in biology learning can foster students' critical habits in choosing food, with recommendations for improvement in action planning assistance and strengthening understanding of nutrition concepts.